Achados ecocardiográficos em microcefálicos por vírus zika de serviço do estado de Sergipe, Brasil - Costa, Isabela Soares (2018)
Goal: The presence of cardiac changes as a component of the congenital syndrome caused by by the Zika virus is not yet known. This study aims to describe the findings of the presumptive echocardiographic evaluation of infants with microcephaly related to the Zika virus of the State of Sergipe, Brazil. Methods: It is a cross-sectional, descriptive and retrospective observational study that presence of echocardiographic alterations through echocardiographic reports, performed by the same cardiologist in the same device, in infants with perimeter with less than - 2 SD, with maternal serologies for other negative causes and with diagnostic neuroimaging of CNS malformations. Results: Of the 101 patients investigated, 62 had a confirmed diagnosis of microcephaly Zika virus and of these, 54.2% presented some echocardiographic alteration, being the the most frequent patent foramen ovale (42.4%), with prevalence practically doubled in the general population, followed by the persistent arterial duct (10.6%), within the estimated prevalence for such finding. Conclusion: Because of the similar embryonic origin of these structures in relation to the neural tube, study may be the starting point for suggesting specific viral neurotropism. More studies are needed to confirm cardiac involvement as a component of the Zika virus congenital syndrome.